2007
DOI: 10.1093/jn/137.4.1106
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fish in Food-Based Strategies to Combat Vitamin A and Mineral Deficiencies in Developing Countries1,

Abstract: Fish is important in the diets and livelihoods of many poor people suffering from vitamin and mineral deficiencies. In this article, fish intake in rural Bangladesh and Cambodia and the vitamin A, calcium, iron, and zinc contents and nutrient bioavailability of commonly consumed species are presented. The contribution of these species to nutrient intakes as well as their potential to meet dietary recommendations are presented and discussed. Data from consumption surveys were analyzed to obtain fish intake by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
159
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(161 citation statements)
references
References 12 publications
1
159
1
Order By: Relevance
“…Some of these small fish (such as mola (Amblypharyngodon mola), darkina (Esomus danricus), sardines and pilchards, anchovy, seabass, tilapia) contain high levels of minerals such as calcium, phosphorus, iodine, zinc, iron and selenium, which are low in other foods. The potential contribution that fish (even in small quantity) can therefore offer to address multiple micronutrient deficiencies is now being recognized (e.g., Roos et al 2007;Kawarazuka and Béné 2011;Thilsted 2012). For instance, the high level of iodine found in fish can help prevent iodine deficiency which is known to cause cretinism (stunted growth and mental retardation).…”
Section: Fish -Beyond Protein…mentioning
confidence: 99%
“…Some of these small fish (such as mola (Amblypharyngodon mola), darkina (Esomus danricus), sardines and pilchards, anchovy, seabass, tilapia) contain high levels of minerals such as calcium, phosphorus, iodine, zinc, iron and selenium, which are low in other foods. The potential contribution that fish (even in small quantity) can therefore offer to address multiple micronutrient deficiencies is now being recognized (e.g., Roos et al 2007;Kawarazuka and Béné 2011;Thilsted 2012). For instance, the high level of iodine found in fish can help prevent iodine deficiency which is known to cause cretinism (stunted growth and mental retardation).…”
Section: Fish -Beyond Protein…mentioning
confidence: 99%
“…As a consequence, several studies have indicated the actual nutrient content of the edible part by reflecting the local methods used to clean and prepare the fish for the meal (e.g. leaving or cutting off the head, removing a part of the viscera) and correcting the calculation for plate waste after meals (8,(23)(24)(25)32) (see Table 2 for details).…”
Section: Lipidsmentioning
confidence: 99%
“…In contrast, a large diversity of fish species (more than 270), particularly small indigenous fish species (SIS, growing to a maximum length of 25 cm) are available from inland capture fisheries. Unlike large fish, many of these SIS, which are consumed whole with head and bones, provide a significant source of bioavailable calcium, zinc, iron and vitamin A (Bogard et al 2015;Roos et al 2007a). Combining SIS with large species in homestead pond polyculture, offers opportunity to increase household dietary diversity and micronutrient intake (Bogard et al 2015;Thilsted 2012a).…”
Section: Introductionmentioning
confidence: 99%